SiPM cross-talk in liquid argon detectors - Boulay, M. G.; Camillo, V.; Canci, N.; Choudhary, S.; Consiglio, L.; Flammini, A.; Galbiati, C.; Ghiano, C.; Gola, A.; Horikawa, S.; Kachru, P.; Kochanek, I.; et al. (Frontiers in Physics, 2023)
SiPM-based readouts are becoming the standard for light detection in particle detectors given their superior resolution and ease of use with respect to vacuum tube photo-multipliers. However, the contributions of noise detection such as the dark rate, cross-talk, and after-pulsing (AP) may significantly impact their performance. In this work, we present the development of highly reflective single-phase argon chambers capable of displaying light yields up to 32 photo-electrons per keV, with approximately 12 being primary photo-electrons generated by the argon scintillation, while the rest are accounted by optical cross-talk. Furthermore, the presence of compound processes results in a generalized Fano factor larger than 2 already at an over-voltage of 5 V. Finally, we present a parametrization of the optical cross-talk for the FBK NUV-HD-Cryo SiPMs at 87 K that can be extended to future detectors with tailored optical simulations.